Engineered Porous Beta-Cyclodextrin-Loaded Raloxifene Framework with Potential Anticancer Activity: Physicochemical Characterization, Drug Release, and Cytotoxicity Studies - Alwattar JK; Mehanna MM (International Journal of Nanomedicine)
Jana K Alwattar,1,2 Mohammed M Mehanna3,4 1Department of Pharmaceutical Sciences, School of Pharmacy, Lebanese International University, Beirut, Lebanon; 2Pharmaceutical Nanotechnology Research Lab, Faculty of Pharmacy, Beirut Arab University, Beirut, Lebanon; 3Department of Pharmaceutical Sciences, School of Pharmacy, Lebanese American University, Byblos, Lebanon; 4Department of Industrial Pharmacy, Faculty of Pharmacy, Alexandria University, Alexandria, EgyptCorrespondence: Mohammed M Mehanna, Department of Pharmaceutical Sciences, School of Pharmacy, Lebanese American University, Byblos, Lebanon, Tel +96171708661, Email mohammed.mehanna@lau.edu.lb; mohamed.mehanna@alexu.edu.egBackground: Cancer ranks as the second most common cause of mortality as depicted by the World Health Organization, with one in six deaths being cancer-related mortality. Taking the lead in females, breast cancer is the most common neoplasm. Raloxifene, a selective estrogen receptor modulator, has been utilized as a chemotherapeutic agent for the treatment of breast cancer in postmenopausal women. However, its poor aqueous solubility hinders its clinical applications. Beta-cyclodextrin-based framework is a novel class of nano-vectors that used to potentiate the solubility and dissolution rate of poorly soluble drugs.Aim: The present study investigates the solubility and dissolution rate enhancement as well as the potential cytotoxic activity of raloxifene-loaded nanosponges formulation.Methods: The fabrication and optimization of cyclodextrin nanosponges crosslinked with diphenyl carbonate was portrayed through stoichiometric selection of cyclodextrin-to-crosslinker ratio. The complexation phenomenon and nanosponges formation were validated using FTIR, PXRD, TEM, and SEM examination.Results: Raloxifene-loaded nanosponges exhibited a 440± 8.5 nm particle size, a negative zeta potential of 25.18± 2.3 mV and a partial drug incorporation. Moreover, the drug loaded nanosponges demonstrated an in-vitro significantly enhanced dissolution behavior. Furthermore, the in-vitro cytotoxicity of the raloxifene-loaded nanosponges on MCF-7 breast cancer cell lines was statistically significant compared to the complex-free raloxifene.Conclusion: The cytotoxic behavior provided evidence that the incorporation of raloxifene within the nanosponges structure enhanced its anticancer activity and represents a potential nanocarrier for anticancer agent delivery.Keywords: raloxifene, nanosponges, anticancer, beta-cyclodextrin, breast cancer